The existence of two genes between infB and rpsO in the Escherichia coli genome: DNA sequencing and S1 nuclease mapping. - Sands, J F (1988)
A number of genes encoding proteins involved in transcription and translation are clustered between 68 and 69 minutes on the Escherichia coli genome map and are transcribed clockwise as two operons: the metY operon, containing metY, P15A, nusA, infB; and about a kilobase further downstream, the rpsO and pnp operon. The DNA sequence between infB and rpsO was determined and two open reading frames were detected which code for proteins of 15,200 (P15B) and 35,091 (P35) daltons. Maxicell analysis showed a relatively strong expression of P15B whereas P35 was synthesized more weakly. An overlap of the termination codon of P15B and the initiator codon for P35 suggests that translation of P15B and P35 may be coupled. S1 nuclease mapping of in vivo transcripts between infB and rpsO provided no evidence for major promoters but detected a moderately efficient rho-independent terminator between infB and P15B. The results indicate that P15B and P35 are expressed as part of the metY operon, but that some transcriptional read through into the rpsO operon also occurs, thereby, functionally linking the expression of these two complex systems.